2008
DOI: 10.2188/jea.je2008006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Disease Patterns in Northern Malawi: Epidemiologic Transition Perspective

Abstract: BackgroundCardiovascular disease (CVD) is a strongly emerging problem in developing countries. The documentation and prediction of CVD patterns are important for policy makers if actions are to be taken to curb this problem. We aimed to document the current CVD patterns in Malawi, and associate these patterns to the theory of epidemiologic transition as a means of predicting future CVD patterns.MethodsWe retrospectively analyzed the data recorded in the register of the cardiac clinic in Mzuzu Central Hospital-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 5 publications
8
46
1
Order By: Relevance
“…South West Ethiopia had cardiomyopathy. This result is also in agreement with a study in Malawi by Soliman et al [34]; they found the prevalence of cardiomyopathy to be 9.8%. In a study of 708 cardiac patients at the National Cardiothoracic Centre at the Korle Bu Teaching Hospital, Accra, Amoah et al [9] reported a comparable proportion of cases with cardiomyopathy (14.6%).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…South West Ethiopia had cardiomyopathy. This result is also in agreement with a study in Malawi by Soliman et al [34]; they found the prevalence of cardiomyopathy to be 9.8%. In a study of 708 cardiac patients at the National Cardiothoracic Centre at the Korle Bu Teaching Hospital, Accra, Amoah et al [9] reported a comparable proportion of cases with cardiomyopathy (14.6%).…”
Section: Discussionsupporting
confidence: 93%
“…The disparity could be partly due to difference in case definition, sample size and the population studied. The major risk factors for coronary artery disease identified in our cardiac patients were hypertension, diabetes mellitus and obesity; which compares well with previous studies done in Ghana [9] and some other African countries [34].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations